The influence of social media influencer marketing on consumer purchasing behavior: Its performance in raising brand awareness and increasing sales in Dhaka - Sultana, Jesmin (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.